The Immunoregulatory Effects of Caffeic Acid Phenethyl Ester on the Cytokine Secretion of Peripheral Blood Mononuclear Cells From Asthmatic Children - Leticia Bautista Sy; Li-King Yang; Chiau-Juno Chiu; Wen-Mein Wu (Elsevier, 2011)
Asthma is a chronic inflammatory disease of the airways for which current treatments are mainly based on pharmacological interventions, such as glucocorticoid therapy. Our objective was to study the immunoregulatory effects of caffeic acid phenethyl ester (CAPE, a phytochemical synthesized from propolis) on cytokine secretion of peripheral blood mononuclear cells (PBMCs) from asthmatic children. Methods: PBMCs from asthmatic children (5.5±3.3 years old, n=28) and healthy children (5.6±2.8 years old, n=23) were co-cultured with CAPE in vitro with and without phorbol-12-myristate-13-acetate-ionomycin. Results: Our results show that predominant interleukin 4 (IL-4) and interferon-gamma secretion of cultured supernatant were detected in healthy donors compared with asthmatics. In the presence of phorbol-12-myristate-13-acetate-ionomycin, with or without CAPE treatment, the asthmatic children showed significantly decreased levels of IL-10 secretion compared with the healthy controls. However, CAPE significantly decreased IL-10 and interferon-gamma in healthy donors. There was a slight but not statistically significant reduction of IL-4 secretion in CAPE-treated PBMCs compared with untreated control PBMCs from the healthy children. Our data also shows that CAPE significantly enhanced transforming growth factor-beta 1 production from PBMCs from asthmatic children. Conclusion: The immunoregulatory effects of CAPE on human PBMCs may be through the induction of regulatory T cells, as evidenced by the enhanced transforming growth factor-beta 1 production from PBMCs from asthmatic children in our study.